2008
DOI: 10.1590/s0066-782x2008001300003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e abordagem cirúrgica da estenose supravalvar pulmonar pós-operação de jatene para transposição das grandes artérias

Abstract: SummaryBackground: The Transposition of the Great Arteries is the most frequent congenital cyanogenic cardiopathy in the neonatal period, corresponding to 7% of all congenital cardiopathies. Among the operations for surgical treatment, the Jatene operation, with arterial correction, is the treatment of choice. During the late postoperative evolution, some problems were observed, with the most common being the occurrence of supravalvular stenosis at the neopulmonary, regardless of the type of surgical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Previous studies have reported that significant PS was found in 10-30% patients 8)10)11). In recent work described by Jatene et al,9) severe supravalvar PS (a mean gradient of >60 mmHg) was reported in 7.4% of his cases, and all patients underwent reoperation. We observed significant PS in 7.1% of patients who underwent reoperation or intervention.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have reported that significant PS was found in 10-30% patients 8)10)11). In recent work described by Jatene et al,9) severe supravalvar PS (a mean gradient of >60 mmHg) was reported in 7.4% of his cases, and all patients underwent reoperation. We observed significant PS in 7.1% of patients who underwent reoperation or intervention.…”
Section: Discussionmentioning
confidence: 77%
“…It is noteworthy that the child was totally asymptomatic, but there must always be concern to avoid the increase of the right ventricular mass, arrhythmias and sudden death [1,2].…”
Section: Diagnosismentioning
confidence: 99%
“…A Transposição das Grandes Artérias -TGA corresponde, aproximadamente, de 7-10% entre as cardiopatias congênitas cianogênicas, tendo sida considerada uma cardiopatia de evolução letal, por levar ao óbito 50% das crianças no primeiro mês de vida, e mais de 90% no primeiro ano, antes do surgimento de técnicas para sua correção. Com os avanços no conhecimento da fisiopatologia cardíaca e as descobertas tecnológicas nas últimas décadas, ocorreu redução da taxa de morbidade e aumento da sobrevida (BUENO, KIMURA, 2008;JATENE et al, 2008) Normalmente, a mistura do sangue entre as duas circulações acontece através da comunicação entre os átrios e ventrículos, ou grandes artérias. No entanto, uma malformação anatômica impedindo fisiologicamente essa mistura, é incompatível com a vida.…”
Section: Introductionunclassified
“…No entanto, uma malformação anatômica impedindo fisiologicamente essa mistura, é incompatível com a vida. Assim a transposição das grandes artérias corresponde à situação em que as artérias coronárias têm sua origem no ventrículo direito e o tronco pulmonar no ventrículo esquerdo, mesmo mantendo-se uma correta disposição das câmaras cardíacas (CRUZ et al, 2013;JATENE;JANETE;MONTEIRO, 2005).…”
Section: Introductionunclassified